Praktik Green Banking dalam Memediasi Pengaruh Corporate Social Responsibility terhadap Kinerja Perusahaan Perbankan - Hayu Mas Wrespatiningsih; Luh Putu Mahyuni (Universitas Pamulang, 2022)
A company must pay attention to the surrounding environment so that the activities carried out by the company do not have a negative impact on the surrounding environment. This research aims to provide empirical evidence of the role of green banking practices in mediating the effect of corporate social responsibility (CSR) on the performance of banking companies. This research was conducted on banking companies listed on the IDX for the period 2018 to 2020. This research is included in quantitative research with the type of data used being secondary data. Data was collected by the documentation method. The population of this research is all banking companies listed on the IDX for the period 2018 to 2020 totalling 44 companies. The data were then analyzed using path analysis techniques. This study provides empirical evidence that CSR has a significant positive effect on green banking practices, but this study did not succeed in obtaining a significant effect of CSR on the performance of banking companies. The performance of banking companies is significantly affected by green banking practices. This study also finds that green banking practices are not significantly able to mediate the effect of CSR on the performance of banking companies